Kehidupan Wanita Mesir Dalam Novel Al-Ifthor Al-Akhir Karya Hisyam Syaban Perspektif Ian Watt - Sawitri, Sri Endah; Fitriani, Laily (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
Egyptian society is known as a nation that has a good culture from ancient times, it is not only good that it turns out that Egyptian society also has other cultures. This study aims to find out how the life of Egyptian women in the novel Al Ifthor Al Akhir Karya Hisyam Syaban, according to Ian Watt's perspective. This study discusses how the description of the life of Egyptian women is in the novel. The method used in this research is descriptive descriptive research method. The data taken by the researcher is in the form of words that describe the reflection of the life of women in Egypt. The results of the study show that the researcher found 2 data from the novel Al Ifthor Al Akhir which reflects that there is peace for women in the Egyptian area, 3 data states that women are in a powerless position and 3 data states that many affairs have occurred.